SURGICAL TREATMENT OF PRIMARY MALIGNANT TUMORS OF THE TRACHEA - I. V. Mosin; V. A. Volchkov; A. A. Gorokhov; O. V. Lukina; N. V. Mosina; A. A. Bazhanov (Вестник хирургии имени И.И. Грекова)
The authors have performed 18 circular resections of the trachea (CRT) for adenocystic cancer and typical carcinoid. In 10 of these patients more than 5 cm of the tracheal segment were ablated. Postoperative radiotherapy was made on 8 patients with adenocystic cancer with lengthy CRT. Immediate and long-term results were good that allowed the authors to recommend a single-stage circular resection of the trachea in treatment of high differentiated forms of cancer.